(untitled) (Journal of Building and Road Research, 2021)
In search for adequate and affordable housing based on appropriate local building materials and technologies, the National Fund for Housing and Rehabilitation (NFHR) has invited research institutes, professional associations and practitioners to give their suggestions and recommendations in this regard. Demonstration models were developed to show the appropriateness of some technologies and materials and the extent of its affordability. The purpose of this study is to carry out a comparative analysis between some of these different technologies in terms of economical and environmental contexts using Ecotect software. According to the analysis results, selected materials for walling and roofing are ranked based on their performance in terms of annual energy required, passive comfort, heat gains, and passive breakdown of heat gains and losses.